2002
DOI: 10.1103/physrevstab.5.061001
|View full text |Cite
|
Sign up to set email alerts
|

Luminosity optimization near the beam-beam limit by increasing bunch length or crossing angle

Abstract: We discuss the choice of bunch length and crossing angle near the beam-beam limit in a storage-ring collider. First, we derive expressions for the tune shifts of either bunched or continuous round beams which are induced by a single collision with arbitrary crossing angle and bunch length and for the associated luminosities. Then, considering two collision points with alternating planes of crossing, we demonstrate that, if the total beam-beam tune shift is held constant, the collider luminosity increases as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Moreover, the horizontal tune shift x drops like 1= z . However, unlike [12,13], in the present crab-waist scheme the Piwinski angle is increased by decreasing the horizontal beam size and increasing the crossing angle. In this way we can gain in luminosity as well, and the horizontal tune shift decreases.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the horizontal tune shift x drops like 1= z . However, unlike [12,13], in the present crab-waist scheme the Piwinski angle is increased by decreasing the horizontal beam size and increasing the crossing angle. In this way we can gain in luminosity as well, and the horizontal tune shift decreases.…”
mentioning
confidence: 97%
“…It has been also proposed for hadron colliders [12,13] to increase the bunch length and the crossing angle. In such a case, if it were possible to increase N proportionally to z , the vertical tune shift y would remain constant, while the luminosity would grow proportionally to z ; see (1).…”
mentioning
confidence: 99%
“…The crossing angle does not only reduce the geometric overlap of the colliding bunches, but it also reduces the beam-beam tune shift induced by the wanted central collision. For round beams with alternating planes of crossing in two IPs the reduction of the beam-beam tune shift is approximately given by the same factor R  as for the luminosity [39] (see above).…”
Section: Long-range Collisionsmentioning
confidence: 69%
“…[2] formulas are given for the incoherent tune shift due to the beam-beam interaction for particles in the beam center. In Fig.…”
Section: Beam-beam Tune Shiftsmentioning
confidence: 99%
“…He showed that an increase in the crossing angle reduces the beam-beam tune shift and allows a higher line density, which in turn leads to an increased luminosity. Recently, Ruggiero and Zimmermann extended this analysis to bunched beams [2]. They computed the incoherent beam-beam tune shift as a function of crossing angle and bunch length and showed how the luminosity increases at the beambeam limit with an increase in the crossing angle or bunch length.…”
Section: Introductionmentioning
confidence: 99%